1319 Factors Associated with Mortality in Older Patients Sustaining Pelvic or Acetabular Fractures. (12th October 2021) - Harrison, A; Ordas Bayon, A; Chimutengwende-Gordon, M; Fortune, M; Chou, D; Hull, P; Carrothers, A; Rawal, J
Abstract: Introduction: This study aimed to investigate potential factors, including delay to surgical stabilisation, affecting mortality in older patients sustaining pelvic or acetabular (PA) fractures. Method: A retrospective review of the Trauma Audit and Research Network (TARN) database was performed to identify older patients (aged 65 and over) sustaining PA fractures treated surgically in a UK Major Trauma Centre (MTC) between 2015 and 2019. Chi-squared and Fisher tests were used to compare 1-year mortality rates following operative intervention between patients treated within 72-hours and after 72-hours. Kaplan-Meier curves were used to visualise survival probability; significant predictors of survival were found using Cox proportional hazard models. Results: Of 564 older patients with PA fractures, 70 met the inclusion criteria. The mean age was 76.1 years. The overall 1-year mortality rate was 20%. When patients were grouped by time to surgery, there was no statistically significant difference in 1-year mortality. Patients whose surgery was delayed more than 72-hours were more likely to have longer hospital stays (p = 0.002) or to have suffered from polytrauma (p = 0.025). Age, Charlson Co-morbidities Index and pre-op mobility status were associated with statistically significant differences in overall mortality. Patient gender, mechanism of injury, polytrauma and head injury were not significant predictors of mortality. Conclusions: Surgical intervention within 72-hours of injury did not result in decreased mortality in older patients with PA fractures. The 1–year mortality rate between older PA fractures and hip fractures was comparable. Consideration should be given to a combined multidisciplinary approach to managing these patients.